(3cJGH GdfgGjIs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg eSJMb GdMeO hehLHg (B... (3cJGH eGgjI GdWgGQI hcjajI JQJjHgG(B. (3GdWgGQI aj GdTQjYI(B...s
(3BNQgG (B:s
(3aEf CJda Pdc Ydi Pej aj MQRg cGf Ydjg VeGfg aEf CJdag Ydjg hcGf bO CXgQg de jcf Ydjg TjA Ydi MGd(B. (3Je GdcJGHs
(3HChdgG agQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3GdPQjYI HQbe(B: 2141s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis